2020
DOI: 10.1117/1.jbo.25.12.123704
|View full text |Cite
|
Sign up to set email alerts
|

Multiplane differential phase contrast imaging using asymmetric illumination in volume holographic microscopy

Abstract: Significance: Differential phase contrast (DPC) is a well-known imaging technique for phase imaging. However, simultaneously acquiring multidepth DPC images is a non-trivial task. We propose simultaneous multiplane DPC imaging using volume holographic microscopy (VHM). Aim: To design and implement a new configuration of DPC-VHM for multiplane imaging. Approach: The angularly multiplexed volume holographic gratings (AMVHGs) and the wavelength-coded volume holographic gratings (WC-VHGs) are used for this purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As a primarily computational method, phase retrieval has benefited greatly from advances in computing power. The practical application of phase retrieval for QPI therefore began in the 1990s with extensive use of computing resources. , Advances in optical systems further enhanced phase retrieval QPI, including the use of color-multiplexing to obtain phase data from a single image, lens-less phase retrieval with super-resolution reconstruction, and volumetric holography using asymmetric illumination . Looking forward, phase retrieval stands to benefit greatly from future advances in computation.…”
Section: Solving the Fundamental Problem Of Quantitative Phasementioning
confidence: 99%
“…As a primarily computational method, phase retrieval has benefited greatly from advances in computing power. The practical application of phase retrieval for QPI therefore began in the 1990s with extensive use of computing resources. , Advances in optical systems further enhanced phase retrieval QPI, including the use of color-multiplexing to obtain phase data from a single image, lens-less phase retrieval with super-resolution reconstruction, and volumetric holography using asymmetric illumination . Looking forward, phase retrieval stands to benefit greatly from future advances in computation.…”
Section: Solving the Fundamental Problem Of Quantitative Phasementioning
confidence: 99%
“…It has been shown that a prerecorded knife edge filter can also be used to obtain phase contrast images and the advantages of such a system were discussed. Recently a multiplane qualitative DPC imaging technique using volume holographic grating was proposed [32]. Simultaneous multiplane DPC images were acquired by the use of an angularly multiplexed volume holographic grating [33,34].…”
Section: Qualitative Differential Phase Contrast Microscopymentioning
confidence: 99%